Paramedic Exposure to Out-of-Hospital Cardiac Arrest Resuscitation Is Associated With Patient Survival - Dyson, K.; Bray, J.; Smith, K.; Bernard, S.; Straney, L.; Finn, Judith (2016)
BACKGROUND: Although out-of-hospital cardiac arrest (OHCA) is a major public health problem, individual paramedics are rarely exposed to these cases. In this study, we examined whether previous paramedic exposure to OHCA resuscitation is associated with patient survival. METHODS AND RESULTS: For the period 2003 to 2012, we linked data from the Victorian Ambulance Cardiac Arrest Registry to Ambulance Victoria's employment data set. We defined exposure as the number of times a paramedic attended an OHCA where resuscitation was attempted in the 3 years preceding each case. Using a multivariable model adjusting for known predictors of survival, we measured the association between paramedic OHCA exposure and patient survival to hospital discharge. During the study period, there were 4151 paramedics employed and 48?291 OHCAs (44% with resuscitation attempted). The median exposure of all paramedics was 2 (interquartile range 1-3) OHCAs/year. Eleven percent of paramedics were not exposed to any OHCA cases. Increased paramedic exposure was associated with reduced odds of attempted resuscitation (P<0.001). In the 3 years preceding each OHCA where resuscitation was attempted, the median exposure of the treating paramedics was 11 (interquartile range 6-17) OHCAs. Compared with patients treated by paramedics with a median of =6 exposures during the previous 3 years (7% survival), the odds of survival were higher for patients treated by paramedics with >6 to 11 (12%, adjusted odds ratio 1.26, 95% confidence interval 1.04-1.54), >11 to 17 (14%, adjusted odds ratio 1.29, 95% confidence interval 1.04-1.59), and >17 exposures (17%, adjusted odds ratio 1.50, 95% confidence interval 1.22-1.86). Paramedic years of experience were not associated with survival. CONCLUSIONS: Patient survival after OHCA significantly increases with the number of OHCAs that paramedics have previously treated.